4 - Uganda’s Vision 2040 and Human Needs Promotion - Balyejjusa, Senkosi Moses (Africa Development, 2021)
In 2013 the President of Uganda Yoweri Kaguta Museveni launched Uganda’s Vision 2040, a thirty-year development master plan which has received both praise and criticism from Ugandans. Although Vision 2040 has received both praise and criticism in almost equal measure, in this article I argue that Vision 2040 does not adequately promote the satisfaction of the human needs of Ugandans, yet the satisfaction of these needs is a prerequisite for achieving genuine development. Using a human needs framework in general, and Doyal and Gough’s intermediate needs in particular, I show that the Vision’s strategies adequately promote the satisfaction of only three intermediate needs of Ugandans, partially promote the satisfaction of seven intermediate needs of Ugandans, and that there is no single strategy to promote the satisfaction of one of the intermediate needs. This is because some of the Vision strategies do not adequately tackle the current and likely future challenges and bottlenecks to the satisfaction of the human needs of Ugandans. This is mainly due to the central role placed on the private capital (sector) in Vision 2040. I argue that in order for Vision 2040 to adequately promote the satisfaction of the human needs of Ugandans, all and not just some of the needs must be adequately satisfied since human needs are interrelated and interdependent. In addition, Vision 2040 should also be in position to satisfy the human needs of all Ugandans and not just some.